The heresy of Jacob Frank: from Jewish messianism to esoteric myth - Michaelson, Jay (Oxford University Press, 2023)
Introduction: The boundary crosser -- "I tell you everything and tell you nothing" : charlatan, fool, deviant, heretic--who was Jacob Frank? -- "I do not look to heaven but at what God does here on Earth" : Frankist antinomianism as materialist skepticism -- "Everything that is of the spirit has to be turned into flesh" : magic, myth, and the material imaginaire -- "To make a man in wholeness, stable and possessing eternal life" : the occult quest for immortality -- "With this deed we go to the naked thing" : sexual antinomianism as mystical messianism -- "We have no need of books of Kabbalah" : rejecting Kabbalah and Sabbateanism -- "The gods of freemasonry will have to do that which those two did" : Frankism as Western esotericism -- "All religions change and go beyond the borders laid down by their ancestors" : foreshadowing secularism and spirituality.